The Effect Of Environmental Factors On The Events Of Restricted Ardes In Age Children Under Five Years - Lies Handayani (Journal of Applied Nursing and Health, 2020)
Acute Respiratory Infection (ARI) is one of the health problems in developing and developed countries. The World Health Organization (WHO) states that under-five mortality is generally caused by infectious diseases, and two-thirds are caused by Acute Respiratory Tract Infection or ARI. Objective To find out the effect of environmental factors on recurrent ISPA occurrence in children under five years of age in the work area of ​​Baolan Health Center, Tolitoli District. The design used in this study is cross-sectional analytic. The population is all mothers who have children with a history of Ispa disease in the last 6 months without complications (asthma, pulmonary tuberculosis, pneumonia). The sample size is 75 respondents using the Simple Random Sampling technique. Independent Variables of research are Environmental Factors. Dependent variable is Repeated Ispa Event based on observation of Toddler Medical Record. Data was collected using a questionnaire, then the data were analyzed using the Logistic Regression test, with a significance level of α 5 0.05. The results showed that p <a with a value of <0.05, this can be seen in Overall Statistics with a significance value of (p) 0.001 which means that there are variables that affect the incidence of recurrent ARI, and when viewed (p) in each independent variables namely ventilation variable has a value (p) of 0.007 occupancy density variable has a value (p) of 0.009, mosquito repellent use variable has a value (p) of 0.038, cooking fuel type variable has a value (p) of 0.073, the variable habit of smoking family members has a value (p) of 0.003. The discussion of this study was ventilation factors, occupancy density, use of medicinal drugs, types of cooking fuel, smoking habits of family members affecting the incidence of recurrent ARI in children under five years of age in the work area of ​​the Baolan Community Health Center, Tolitoli district.